Effects of Cell-Free Fat Extract and Platelet-Rich Fibrin on Scar Maturation in an Experimental Rabbit Ear Wound Model - Wei Z; Zhang M; Chen M; Song Y; Wang Y (Clinical, Cosmetic and Investigational Dermatology)
Zhenni Wei,1,2,* Mingliang Zhang,3,* Minjian Chen,1 Yong Song,1 Yi Wang1 1Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Fujian Obstetrics and Gynecology Hospital, Fuzhou, Fujian, People’s Republic of China; 3Fuzhou First General Hospital Affiliated with Fujian Medical University, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Minjian Chen, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China, Email 1367120447@qq.comBackground: Multiple methods have been used to treat hypertrophic scarring; however, an optimal treatment method remains to be established. We aimed to research and compare the effects of cell-free fat extract (CEFFE) and platelet-rich fibrin (PRF) on hypertrophic scar formation based on histomorphological analysis in this study.Methods: Twelve rabbits were divided into four groups randomly. (CEFFE+PRF group, n=3; CEFFE group, n=3, PRF group, n=3 and Control group, n=3). After the ear hypertrophic scar model were established, the two ears of each rabbit in the four groups were injected with CEFFE 0.05 mL/cm2 + PRF 0.05 mL/cm2, CEFFE 0.1 mL/cm2, PRF 0.1 mL/cm2, and saline 0.1 mL/cm2, respectively. The scar elevation index and histological analysis using hematoxylin-eosin and Masson staining were evaluated after injection on day 40.Results: The CEFFE+PRF group was significantly more effective in the prevention of pathological scar formation than the CEFFE-only, PRF-only, and control groups in terms of capillary count, collagen organization, fibroblast count, and scar elevation index (p< 0.05).Discussion: CEFFE combined with PRF was the most effective treatment for the prevention of hypertrophic scar formation in our study. Keywords: effects of cell-free fat extract, platelet-rich fibrin, hypertrophic scar, rabbit